2021
DOI: 10.1177/2165143421989408
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Virtual Job Interview Skills to College Students With IDD Using Literacy-Based Behavioral Interventions

Abstract: College students with intellectual and developmental disabilities (IDD) face challenges searching for jobs, often lacking communication and social skills needed during formal interviews. The COVID-19 pandemic complicates interviews, forcing students to search online and attend virtual interviews. This study used a multiple probe design across participants to examine the acquisition of literacy-based behavioral interventions (LBBIs) on virtual job interviews. Using a video conference platform, students answered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…See Table 1 for a task analysis of how to create an E-LBBI. Researchers have demonstrated that E-LBBIs can be successfully delivered via student-preferred modes of learning, such as on a tablet or laptop computer (Downey et al, 2021; Hall et al, 2018; Torres et al, 2021). The use of tablets or laptops to display electronic visual media makes interventions, such as E-LBBIs, more accessible and appealing to students (Mechling, 2008; Mechling et al, 2014).…”
Section: Electronic-lbbismentioning
confidence: 99%
See 1 more Smart Citation
“…See Table 1 for a task analysis of how to create an E-LBBI. Researchers have demonstrated that E-LBBIs can be successfully delivered via student-preferred modes of learning, such as on a tablet or laptop computer (Downey et al, 2021; Hall et al, 2018; Torres et al, 2021). The use of tablets or laptops to display electronic visual media makes interventions, such as E-LBBIs, more accessible and appealing to students (Mechling, 2008; Mechling et al, 2014).…”
Section: Electronic-lbbismentioning
confidence: 99%
“…LBBIs have been used to teach a variety of skills to individuals with disabilities aged 3–57 (Bucholz et al, 2008; Hall et al, 2019). Educators have used LBBIs to teach daily living skills (Brady, Honsberger et al, 2016), on-task behavior (Bucholz et al, 2008), self-regulation skills (Hall et al, 2019), employment skills (Hall et al, 2018; Honsberger et al, 2019), requesting a classroom accommodation (Hall Pistorio et al, 2021a), safety skills (Kearney et al, 2018), and job interviewing skills (Downey et al, 2021; Torres et al, 2021). LBBIs have been successfully implemented by classroom teachers (Anderson et al, 2016; Flores et al, 2014), pre-service teachers (Hall Pistorio et al, 2021a), job coaches (Hall et al, 2018) and peers (Honsberger et al, 2019; Kearney et al, 2018).…”
mentioning
confidence: 99%